Analysis of the crystallization behaviour of PBT-rich PBT/PET blends under processing conditions - La Carrubba, V; Piccarolo, S; Brucato, V (10th Esaform Conference on Material Forming: Part A(AIP Conference Proceedings Volume 907), 2007)
Among the high-performance polyesters blends PBT/PET blends are expected to exhibit remarkable properties as far as the crystallization behaviour is concerned. The solidification behaviour of a 60/40 w/w PBT/PET blend was studied in a wide range of cooling conditions, according to a Continuous Cooling Transformation (CCT) procedure developed by the authors, aiming to emulate the typical conditions encountered in polymer processing. A set of several samples characterized by an homogeneous structure was prepared by solidification from the melt through spray cooling, and the resulting structure and properties were evaluated by density, Micro Hardness (MH), Wide Angle X-ray Diffraction (WAXD) measurements, to describe their dependence upon the imposed thermal history. The resulting solidification behaviour was then compared to that exhibited by the constituents of the blend (PET and PBT).